Subthalamic nucleus beta and gamma activity is modulated depending on the level of imagined grip force - Fischer, P; Pogosyan, A; Cheeran, B; Green, A; Aziz, T; Hyam, J; Little, S; Foltynie, T; Limousin, P; Zrinzo, L; Hariz, M; Samuel, M; et al. (Elsevier, 2017)
Motor imagery involves cortical networks similar to those activated by real movements, but 2 the extent to which the basal ganglia are recruited is not yet clear. Gamma and beta oscillations 3 in the subthalamic nucleus (STN) vary with the effort of sustained muscle activity. We recorded 4 local field potentials in Parkinson’s disease patients and investigated if similar changes can be 5 observed during imagined gripping at three different ‘forces’. We found that beta activity 6 decreased significantly only for imagined grips at the two stronger force levels. Additionally, 7 gamma power significantly scaled with increasing imagined force. Thus, in combination, these 8 two spectral features can provide information about the intended force of an imaginary grip 9 even in the absence of sensory feedback. Modulations in the two frequency bands during 10 imaginary movement may explain the rehabilitating benefit of motor imagery to improve motor 11 performance. The results also suggest that STN LFPs may provide useful information for brain-12 machine interfaces.